Exploring the Creativity Habitus of Elementary Teacher Education Students within Visual Arts Learning Practices - Probosiwi; Tamás, Kopasz; Muryasari, Desiana; Barnawi, Erizal; Effendi, Dian (The Indonesian Institute of Science and Technology Research, 2025)
The purpose of this article is to describe the creativity of elementary teacher education students in learning practices analyzed through the concept of habitus. The research method used is a qualitative type with content analysis techniques. Data collection techniques were carried out through semi-structured interviews, non-participatory observation, and documentation review. The research subjects were students, and the object of the research was the practice of visual arts learning in elementary schools. The sources interviewed consisted of classroom teachers. The results indicate that visual arts teaching practices in elementary schools are based not only on teachers' academic abilities but also on adequate facilities and infrastructure. The position of habitus in teaching practices in elementary schools makes students an audience that contributes to social practices that strengthen the creativity process based on four stages: person, process, product, and press. The combination of the students' understanding of aesthetics and habitus can support the creative process in the practice of teaching visual arts to elementary school students.